The effect of postoperative pain on postoperative blood loss after sequential bilateral total knee arthroplasty - Kim, So Yeon (The Korean Society of Anesthesiologists, 2011)
BACKGROUND: Bilateral total knee arthroplasty is generally accompanied by a significant amount of blood loss. We investigated the relationship between the intensity of pain and the amount of blood loss in the early postoperative period after bilateral total knee arthroplasty. METHODS: A prospective study was conducted on 91 patients who underwent elective sequential bilateral total knee arthroplasty for osteoarthritis. All patients received combined spinal and epidural anesthesia. Patients were divided into three groups based on their scores on the verbal numerical rating scale (VNRS) for pain at 6 hours postoperatively. The VNRS was classified as follows; mild pain (n = 34, VNRS score 0-4), moderate pain (n = 24, VNRS score 5-6), and severe pain (n = 33, VNRS score 7-10). We compared the mean arterial pressures and the amount of blood loss during the first 24 postoperative hours in the three groups. Factors influencing postoperative blood loss were analyzed. RESULTS: Postoperative mean arterial pressures and blood loss were not different among the groups. Of the factors examined, the amount of postoperative blood loss was only dependent on the amount of intraoperative blood loss (P = 0.001). CONCLUSIONS: Early postoperative pain has no effect on postoperative blood pressure and the amount of blood loss after bilateral total knee arthroplasty. For postoperative blood loss, intraoperative blood loss is the main determinant.